Evaluating Communication Practices between Dentists and Dental Technicians - Hassan, Hammad; Hassan Tariq; Aneela Qaisar; Muhammad Imran Ameer Malik; Aamir Rafique (Journal of University College of Medicine and Dentistry, 2024)
Objectives: To evaluate the effectiveness of current communication practices and the understanding of technicians regarding written prescriptions. Methodology: This Questionnaire based cross-sectional study was conducted in Lahore, from Aug 2023 to May 2024, to assess communication quality between dentists and dental technicians. The sample consisted of 50 dental technicians currently employed in ten different private and public dental laboratories in Lahore, Punjab. The selection of participants was carried out using non-probability convenient sampling. Undergraduate students pursuing dental technology were excluded from the study to maintain a focus on experienced professionals who actively participate in dental restoration processes. Data were collected using a modified standardized questionnaire, including items on demographics and communication quality. Data was collected, reviewed for completeness, and analyzed using SPSS v24. Results: Most dental technicians (n=38, 68%) possess a BSc degree in dental technology with work experience ranging from 1 to 45 years. Communication preferences varied notably across workplace settings. About 46% (n=23) of the technician favored direct communication. There was a significant difference in communication modes between these settings (p=0.001), with a preference for personal visits, particularly among technicians from teaching institutes (n=23, 88.5%). The majority (n=42, 84%) reported positive receptivity from dentists, and 62% (n=31) indicated that communication was encouraged, particularly in teaching institutes. Issues regarding blank prescription cards were mixed, with 36% (n=18) never receiving them and 50% (n=25) consulting clinicians in such cases. Only 36% (n=18) of technicians felt they received sufficient information. Conclusion: Most technicians prefer direct communication from dentists, particularly in teaching institutes, compared to those in commercial labs who favor phone calls. A major concern was the lack of sufficient information and blank patient prescriptions from dentists. Addressing these gaps through standardized protocols, modern digital tools, and enhanced training can improve patient outcomes.